Effectiveness of the home-based alcohol prevention program "In control: No alcohol!": study protocol of a randomized controlled trial - Verdurmen Jacqueline EE; Schulten Ingrid; Lichtwarck-Aschoff Anna; van der Vorst Haske; Mares Suzanne HW; Otten Roy; Engels Rutger CME (BMC, 2011)
Abstract Background In the Netherlands, children start to drink at an early age; of the Dutch 12-year olds, 40% reports lifetime alcohol use, while 9.7% reports last-month drinking. Starting to drink at an early age puts youth at risk of developing several alcohol-related problems later in life. Recently, a home-based prevention program called "In control: No alcohol!" was developed to delay the age of alcohol onset in children. The main aim of this project is to conduct a Randomized Controlled Trial (RCT) to evaluate the effectiveness of the program. Methods/Design The prevention program will be tested with an RCT among mothers and their 6 grade primary school children (11-12 years old), randomly assigned to the prevention or control condition. The program consists of five printed magazines and an activity book designed to improve parental alcohol-specific socialization. Parent-child dyads in the control group receive a factsheet information brochure, which is the standard alcohol brochure of the Trimbos Institute (the Netherlands Institute for Mental Health and Addiction). Outcome measures are initiation of alcohol use (have been drinking at least one glass of alcohol), alcohol-specific parenting, susceptibility to drinking alcohol, alcohol expectancies, self-efficacy, and frequency and intensity of child alcohol use. Questionnaires will be administered online on secured Internet webpages, with personal login codes for both mothers and children. Mothers and children in both the experimental and control condition will be surveyed at baseline and after 6, 12, and 18 months (follow-ups). Discussion The present study protocol presents the design of an RCT evaluating the effectiveness of the home-based "In control: No alcohol!" program for 6 grade primary school children (11-12 years old). It is hypothesized that children in the prevention condition will be less likely to have their first glass of alcohol, compared to the control condition. When the prevention appears to be effective, it can easily and relatively quickly be implemented as a standard alcohol prevention program on a large scale. Trial registration Nederlands Trial Register NTR2564